Collective Anger and Digital Mobilization: An Analysis of Social Movements in the Case of Mass Protests in Pati Regency, Indonesia, 2025 - Muliono Muliono (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze a social movement within the cases of mass protests that occurred in Pati Regency in 2025. This movement involved various social classes actors at the local level and was organized within a short timeframe. This study employed an observational method focused on online social media and discourse analysis approach. Data were obtained through digital media platforms such as Twitter, Instagram, and mainstream media. The findings show that, first, the social movement was grounded in collective anger toward the authorities’ behavior, which was perceived as insensitive to public sentiment and aspirations. Consequently, the protest mobilized diverse segments of society. Second, digital media played a pivotal role in shaping collective behavior and mobilizing the social movement. Third, the protest movement is classified into three forms they are digital space indignation, massive logistical support provided by the local community, and direct protest actions against the Regent. These actions also involved instances of violent conflict. The collective anger in the mass protests of Pati Regency reflects an evolving public sentiment that is formed and digitally distributed. Moreover, the protest signifies mass indignation toward a political system that tends toward authoritarianism. This study contributes to the study of new social movements and offers practical insights for policymakers by providing an understanding of how the dynamics of collective emotion specifically public anger can evolve into organized social movements through digital networks.